Grid-connected inverter with synthetic inertia capability in DC coupled PV-BESS systems - Xu, Yuqi (Nanyang Technological University, 2024)
As the global transition towards renewable energy sources intensifies, photovoltaic (PV) technology stands out as a promising solution for clean electricity generation. However, the stochastic and intermittent nature of solar power generation poses challenges, necessitating the integration of battery energy storage systems (BESS) to stabilize PV system output. While traditionally AC-Coupled PV-BESS systems have been prevalent, DC-Coupled configurations have gained traction recently, offering advantages such as reduced capital expenditure costs. However, in DC-Coupled systems, the synthetic inertia capabilities of the BESS inverter are unavailable. This study addresses this gap by investigating the feasibility of incorporating synthetic inertia capability into grid-connected inverters within DC-Coupled PV-BESS systems. Through the establishment of a corresponding system model using PLECS software, this research aims to assess the technological feasibility of this integration, thereby contributing to the enhancement of grid stability and reliability amidst the growing reliance on renewable energy sources.